Nove vrste v favni metuljev (Lepidoptera) Slovenije - Lasan, Mojmir (Acta entomologica slovenica (Ljubljana), 2000)
25 Macrolepidoptera species, newly recorded in the Slovenian fauna, are listed: one belonging to Drepanidae, 8 to Geometridae, 14 to Noctuidae, one to Lymantriidae and one to Arctiidae. Unexpected were the finds of the southern species Charissa certhiatus (Rebel & Zerny, 1931) (Geometridae) and Chersotis elegans (Eversmann, 1837) (Noctuidae), with the nearest known localities up to now in the southern Velebit in Croatia. Included is also Phytomertra amata (Butler, 1878) (Noctuidae), found in Slovenia by the German Lepidopterist Lars Kühne, which is new to Europe.
Keywords: favna; metulji; Slovenia; Slovenija; zoologija; zoology